2014
DOI: 10.3855/jidc.3199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter among goats and retail goat meat in Congo

Abstract: Background: The prevalence of Campylobacter jejuni and Campylobacter coli was determined in goat and goat meat sold at retail outlets in Lubumbashi, Democratic Republic of Congo (DR Congo). Methodology: A total of 644 samples, including 177 goat meat, 86 goat stomachs, 139 ready to eat (RTE) goat skewers, and 242 goat faecal samples were examined for the presence of Campylobacter jejuni and Campylobacter coli using polymerase chain reaction. Results: Overall, Campylobacter spp. were found in 34.6% of the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
3
20
4
1
Order By: Relevance
“…e overall mean prevalence was 31.2%, and C. jejuni presented with a higher prevalence (56.2%) than C. coli (38.5%). e highest and lowest prevalence were reported from the Democratic Republic of Congo (DRC) [83] and Ghana [83], respectively. Ethiopia [70] and DRC [83] had the highest frequencies for C. jejuni and C. coli, respectively ( Table 2).…”
Section: Campylobacter Spp In Animals and Contamination Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…e overall mean prevalence was 31.2%, and C. jejuni presented with a higher prevalence (56.2%) than C. coli (38.5%). e highest and lowest prevalence were reported from the Democratic Republic of Congo (DRC) [83] and Ghana [83], respectively. Ethiopia [70] and DRC [83] had the highest frequencies for C. jejuni and C. coli, respectively ( Table 2).…”
Section: Campylobacter Spp In Animals and Contamination Ofmentioning
confidence: 99%
“…e highest and lowest prevalence were reported from the Democratic Republic of Congo (DRC) [83] and Ghana [83], respectively. Ethiopia [70] and DRC [83] had the highest frequencies for C. jejuni and C. coli, respectively ( Table 2). For sheep, data were reported in four articles from three countries.…”
Section: Campylobacter Spp In Animals and Contamination Ofmentioning
confidence: 99%
“…Similarly, Campylobacter recovery from goat carcases has been widely reported in Ethiopian, Ghanaian and Grecian abattoirs (Woldemariam et al, 2009;Lazou et al, 2014;Karikari et al, 2017), raw retail goat meats respectively in Ethiopia and Iran (Dadi and Asrat, 2008;Rahimi et al, 2010), and goat meat has been reported to act as major source of human and environmental contamination by Campylobacter spp. in Congo (a Mpalang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prevalence of 34.6% of Campylobacter spp. was detected in goats slaughtered at Congo and in developing countries such as Iran, Pakistan, and Malaysia, and Campylobacter was reported in 9.4% of goat meat [ 37 ].…”
Section: Discussionmentioning
confidence: 99%